Ocenianie pracowników metodą 360 stopni - wybrane problemy - Chomątowska, Barbara (360-degree employees appraisal - selected problems, 2007)
Traditionally, performance appraisal has been limited to a feedback between employees and firstlevel supervisors. However, with the increased focus on organisational change and management skills needed to carry it out, the emphasis has shifted to employee feedback from the full circle of sources called “360-degree assessment”. This full circle of feedback sources consists of: supervisors, subordinates, internal and external customers, peers and self assessment. The following pages discuss the essence of 360-degree assessment process, that takes part in a 360-degree approach and how we can take advantages of feedback from multiple sources.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (5); 2007; nr 1187, s. 225-233